The Riviera, exposed : an ecohistory of postwar tourism and North African labor - Harp, Stephen L. (Histories and cultures of tourism., 2022)
"This history of the French Riviera examines the ecological and social impacts of mass tourism after World War II. Much of the focus is on the technologies embedded in roads, airports, hotels, water lines, sewers, beaches, and marinas, as well as the North African laborers who built and maintained them"--